O25 'Side chicks', and 'side dicks': understanding typologies and drivers of concurrent partnerships to prevent sti transmission among people of black caribbean ethnicity in england. (8th June 2017) - Wayal, Sonali; Mercer, Catherine; L. Gilbart, Victoria; Garnett, Emma; J. Sutcliffe, Lorna; Weatherburn, Peter; Hughes, Gwenda
Abstract : Introduction: In Britain, STI diagnoses rates and concurrent partnerships are higher among black Caribbeans than other ethnic groups. Concurrency (having sexual partnerships overlapping in time), especially when condoms are not used, can enhance STI transmission probabilities. We sought to understand concurrency typologies and drivers among black Caribbeans in England. Methods: 52 black Caribbeans (n=20 men) aged 15–70 years were recruited from community settings and STI clinics. 4 audio-recorded focus group discussions (n=28 participants) and in-depth interviews (n=24) were conducted from June 2014–December 2015. Transcribed data were thematically analysed to identify concurrency typologies and reasons. Results: Open, situational, and experimental concurrent partnerships were described. Open concurrent partnerships involved having a main partner and additionally men and women having sex with ' side chicks'/'thots' and 'side dicks', respectively. Situational partnerships involved sex with an ex-partner, especially their child's parent, while also having another partner. These partnerships were usually long-term, and condomless sex was common due to emotional attachment, to ' entice' the ex-partner back, or because the relationship was founded on sexual pleasure. Experimental partnerships, common among single participants who were unsure about the type of partner to settle down with, were usually short-term and mostly involved condom use. Concurrency was perceived to be normalised in black Caribbean popular music, on social media, and fuelled by ease of ' ordering sex via app' . Discussion: Understanding of different types of concurrent partnerships experienced by black Caribbeans during clinic consultations can increase the likelihood of effective partner notification. Interventions addressing normative drivers of concurrency are also needed.